Between Autonomy and Paternalism: Attitudes of Nursing Personnel Towards Jehovah's Witnesses' Refusal of Blood Transfusion - Jan Domaradzki; Katarzyna Głodowska; Piotr Jabkowski (Frontiers Media S.A., 2023)
Objectives: The study describes the attitudes of Polish nursing personnel towards Jehovah's Witnesses' (JWs') refusal to receive blood and blood products.Methods: We developed an online survey assessing nurses' knowledge and attitudes towards JWs' refusal of blood transfusion in a life-threatening condition. It also examined nurses' attitudes towards ethical and legal issues associated with JWs' refusal of blood transfusions. These questions were explored using a sample of 202 Polish nurses.Results: Nurses' knowledge of JWs' stance towards blood transfusions is inadequate and they tended to be ill-disposed towards JWs' refusal of blood transfusions. Although most nurses respected adult JW patients' autonomy and supported their right to refuse blood, in the case of JW children they are guided by paternalism. Nurses' attitudes were affected by whether they had children, whether they declared themselves religious, their level of education and prior experience with patients who had refused a blood transfusion.Conclusion: Since most nurses felt unprepared to care for JW patients, this study reveals an urgent need to train nurses in transcultural nursing and increase nurses' cultural competencies, and that this should be incorporated into medical curricula.